Answer:
The answer to your question is below
Explanation:
1.- (2b - 1) (b + 8) = 0
2b - 1 = 0 b + 8 = 0
b = 1/2 b = -8
2.- (x + 3)(x - 12) = 0
x + 3 = 0 x - 12 = 0
x = -3 x = 12
3.- (4b+ 7)(b + 11)
4b + 7 = 0 b + 11 = 0
b = -7/4 b = -11
4.- (k - 8)(k + 6)
k - 8 = 0 k + 6 = 0
k = 8 k = -6
5.- (2n + 12)(5n+ 10)
2n + 12 = 0 5n + 10 = 0
n = -12/2 = -6 n = -10/5 = -2
6.- (w - 3)(3w - 7)
w - 3 = 0 3w - 7 = 0
w = 3 w = 7/3
7.- (6n - 5)(n - 10)
6n - 5 = 0 n - 10 = 0
n = 5/6 n = 10
8.- (n + 12)((4n + 7)
n + 12 = 0 4n + 7 = 0
n = -12 n = -7/4
9.- (3b + 4)(5b - 10)
3b + 4 = 0 5b - 10 = 0
b = -4/3 b = 10/5 = 2
10.- (p - 6)(p + 10)
p - 6 = 0 p + 10 = 0
p = 6 p = -10